183k views
1 vote
Simplify 2i/-4 + 3i please

User Amit Tomar
by
4.8k points

2 Answers

8 votes

Answer:


(6)/(25) -
(8)/(25) i

Explanation:

Assuming you mean


(2i)/(-4+3i)

To simplify, rationalise the denominator

Multiply the numerator/ denominator by the conjugate of the denominator

The conjugate of - 4 + 3i is - 4 - 3i , then

=
(2i(-4-3i))/((-4+3i)(-4-3i)) ā† expand numerator and denominator

=
(-8i-6i^2)/(16-9i^2) [ note that iĀ² = - 1 ]

=
(-8i+6)/(16+9)

=
(6-8i)/(25)

=
(6)/(25) -
(8)/(25) i ā† in standard form

User Stefan Doychev
by
5.0k points
10 votes

2i

āˆ’4

+3i

=

5

2

i

Explanation:

i think it helps

User Preinheimer
by
5.3k points